Sustainable Bonds in Indonesia: A Systematic Literature Review and Future Prospects - Putri, Fatwasari Soeratno; Aryani, Y. Anni; Setiawan, Doddy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
The aim of this study is to review publications on sustainable bonds in Indonesia between 2017 and 2024 using a systematic literature review (SLR). Using the SPAR-4-SLR methodology, 30 relevant articles were sourced from Scopus and Sinta 1 and 2 databases, identified through keywords including